Career perspective: Victor A. Convertino. Issue 1 (December 2015) - Convertino, Victor
Abstract This review focuses on a career of unique opportunities to participate in various areas of research related to extreme physiology and medicine. My experience as a volunteer subject in exercise experiments conducted at NASA included the study of acute and chronic physiological responses and adaptations to exercise in environments of hypoxia, heat stress, and simulated microgravity (bed rest), and eventually to my doctoral work on mechanisms underlying expansion of plasma and blood volume with acute and repeated exercise and heat exposure. My career has taken me to research positions at NASA, the Stanford University School of Medicine, the University of Arizona, and the U.S. Air Force Research Laboratory before assuming my present location at the U.S. Army Institute of Surgical Research. As a result of these multiple experiences across a period of 45 years, I have had opportunities to translate basic research to astronauts, high-performance aircraft pilots, and critically ill patients who are challenged by conditions of extreme physiology and medicine.